2020
DOI: 10.21037/apm-20-1290
|View full text |Cite
|
Sign up to set email alerts
|

Composite lymphoma of cervical lymph nodes with classical Hodgkin lymphoma and diffuse large B cell lymphoma: a case report and literature review

Abstract: Composite lymphoma (CL) is a clinically rare entity, with unknown pathogenic mechanisms. Its diagnosis is quite difficult, and there is currently no proven treatment. In this article, we report a 64-year-old male patient presenting with swelling and mild pain in the bilateral cervical lymph nodes. Radiology revealed lesions only involved the neck. Histological examination showed that the tumor tissue had two components: mixed cellularity classical Hodgkin lymphoma (CHL-MC) and diffuse large B cell lymphoma (DL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…A total of 79 cHL/diffuse large B-cell composite lymphomas from 35 articles were analyzed [ 1 , 3 , 6 , 13 , 14 , 16 , 58 , 64 , 66 , 76 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 ].…”
Section: Resultsmentioning
confidence: 99%
“…A total of 79 cHL/diffuse large B-cell composite lymphomas from 35 articles were analyzed [ 1 , 3 , 6 , 13 , 14 , 16 , 58 , 64 , 66 , 76 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 ].…”
Section: Resultsmentioning
confidence: 99%
“…The ratio of men to women is estimated at about 1.4:1 with a mean age of 51 years [5]. The lymph nodes were the most frequently affected sites (64%), and only 10% of patients have mesenteric involvement [4]. The association of Epstein‐Barr virus and CLs with CHL and DLBCL was observed in about 31% of the cases and was found to be associated with a worsened survival (average survival time 3 vs. 15 months) [5].…”
Section: Figurementioning
confidence: 99%
“…CL with CHL and DLBCL is even more infrequent [3]. Less than 30 cases have been reported in the literature [4,5]. The ratio of men to women is estimated at about 1.4:1 with a mean age of 51 years [5].…”
mentioning
confidence: 99%
“…[1] There exists a situation that more than one type of lymphoma occurs in the same organ or tissue site of the same patient, which is de ned as composite lymphoma (CL) and has been reported in 1-4.7% of all lymphomas. [2,3] CL may consist of HL with NHL [4,5] , B-cell NHL with T-cell NHL [6,7] , or T-cell or B-cell NHL with other histologic types of the same lineage [8] . Especially B-cell lymphoma composite with a T-cell lymphoma is rather rare, but has been referred in recent literature, with the description limited to isolated case report.…”
Section: Introductionmentioning
confidence: 99%
“…[6,7,9,10] The selection of treatment on CL depends mainly on the histological type with high invasiveness and is different from the management of single type lymphoma. [5] In the case of a CL of follicular B-cell and peripheral T-cell types with distinct zone distribution, the response to the treatment with a T-cell lymphoma protocol was poor, which indicated that an optimal therapy for this type of lymphoma remains to be investigated. [6] If an appropriate treatment is not taken in time, the prognosis of the patient will also be poor.…”
Section: Introductionmentioning
confidence: 99%